Health Education About Diabetes Mellitus In Families - Sari, Fitria Kusuma (Journal of International Public Health, 2024)
Diabetes Mellitus (DM) is a disease characterized by blood glucose levels exceeding normal, characterized by fasting and postprandial hyperglycemia, atherosclerosis and microangiopathic vascular disease. DM can be caused by diet or genetic factors. Research conducted in Pahandut Village, Palangka Raya showed that the lack of family knowledge (67%) regarding DM can be a predisposing factor for DM in family members. Education is an effort to get people to behave or adopt healthy behaviors by means of persuasion, persuasion, appeals, invitations, providing information, providing awareness and so on, through activities called health education or promotion. The method of implementing the activity is to use a health education strategy for families in Pahandut Village, Palangka Raya. The activity carried out is to carry out health education to families in Pahandut Village, Palangka Raya. The activity is carried out using the lecture method and Q&A. The health education media used are LCD project tordan leaflets distributed to families. The material provided is about DM disease which includes the definition, causes, signs and symptoms, treatment, complications. During health education, the environment is conducive, families are enthusiastic about listening to health education and actively ask questions when given the opportunity for discussion. The results of the health education evaluation show that families are able to mention and explain again about DM disease as explained during health education. Community service activities carried out by lecturers, nurses and nursing students in families in Pahandut Village, Palangka Raya can be declared successful. Through the results of the evaluation during health education, there was a positive response from families and they were also able to mention again about DM disease as explained.